2020
DOI: 10.3390/ani10112144
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Urinary Big Endothelin-1 in Feline Spontaneous CKD

Abstract: The endothelin-1 (ET-1) system has been implicated in the development and progression of chronic kidney disease (CKD). No information on big ET-1 in feline urine is available. The purpose of this study was to evaluate if urinary big endothelin-1 (bigET-1) is associated with feline CKD. Sixty urine samples were prospectively collected from 13 healthy cats at risk of developing CKD and 22 cats with CKD of different International Renal Interest Society (IRIS) stages (1–4). Urinary bigET-1 was measured using a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…ET and MCP-1 are two types of immune factors closely related to kidney disease that are highly expressed in many kinds of nephropathy and can cause different degrees of damage to the affected kidney in a variety of ways. Therefore, ET and MCP-1 have important significance as clinical diagnostic indicators of kidney disease ( Ciarambino et al., 2021 ; Giraldi et al., 2020 ; Puthumana et al., 2021 ; Srivastava et al., 2021 ). In conclusion, inflammation caused by pesticides may be an important inducer of other secondary diseases, and ET and MCP-1 were the key factors by which pesticides interfered with the immune system in this study.…”
Section: Discussionmentioning
confidence: 99%
“…ET and MCP-1 are two types of immune factors closely related to kidney disease that are highly expressed in many kinds of nephropathy and can cause different degrees of damage to the affected kidney in a variety of ways. Therefore, ET and MCP-1 have important significance as clinical diagnostic indicators of kidney disease ( Ciarambino et al., 2021 ; Giraldi et al., 2020 ; Puthumana et al., 2021 ; Srivastava et al., 2021 ). In conclusion, inflammation caused by pesticides may be an important inducer of other secondary diseases, and ET and MCP-1 were the key factors by which pesticides interfered with the immune system in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Several of the reports describing histopathologic changes in cats with PLN or glomerulonephritis had evidence of fibrin deposition; however, none of the studies that reported histopathology described any micro‐ or macrovascular thrombosis 84,85 . Numerous studies were considered neutral to the PECO question because they did not include a control group, they described arterial thrombosis and did not mention PLN, or they were reports focused on PLN that did not discuss or describe thrombosis 45,48,49,54,59,62,63,66–68,70,86–110 . Although these reports were considered neutral, their collective weight suggests that there is either no association or a very weak association between PLN and arterial thromboembolic complications in cats and that the overall risk of thrombosis in cats with PLN is seemingly low.…”
Section: Peco Question: Protein‐losing Nephropathy (Pln) (Cats)mentioning
confidence: 99%